Physics: A course for 'o' level (second edition) - Chew, Charles; Leong, See Cheng Chow, Siew Foong (Marshall Cavendish Singapore, 2003)
"Physics: A Course for 'O' Level" is a comprehensive textbook designed to help students grasp fundamental physics concepts, providing clear explanations, examples, and practice questions to prepare them for the O-Level Physics exam.